Revitalizing coastal economies through the integration of creative economy and culture for the Tongkole fishermen group, Manado - Maru, Mister Gidion; Kimbal, Rahel Widiawati; Latuni, Glenie (Community Empowerment, 2025)
Karang Ria Beach is the sole natural beach in urban Manado, serving as both a public space and a primary livelihood source for local fishermen. Recently, the Tongkole Fishermen Group has faced declining catches, unstable income, and weak management and marketing capacities. This community partnership program aims to empower the group through an andragogic approach involving training, appropriate technology implementation, and continuous mentoring. Interventions focused on creative economy innovations, including cultural performances, creative competitions, decorative installations, and digital marketing strategies. The results showed a significant increase in management capacity and the emergence of new income streams, evidenced by a 520% rise in economic transaction activities. This program proves that integrating cultural creativity and marketing innovation can effectively revitalize coastal economies. Future recommendations include establishing cooperatives and diversifying experience-based tourism to sustain the program's impact.